Exploring the impacts of climate variability on urban food security in female headed households in KwaZulu-Natal, a study of Durban South Africa - Mkhondo, Penelope Sarona (My University, 2017)
There is substantial evidence to show that the climate has been changing on various scales across the world. The change in climate conditions has had negative impacts for developing countries, particularly poorer communities who use climate-sensitive resources such as urban agriculture which is prone to extreme weather. It is evident that urban agriculture has become a major source of income for a lot of people and its contribution to household food security is significant and in many instances it is increasing. The MSc study investigated the implications of climate variability and change on food production focusing on urban agriculture. It was also of key interest to explore the different adaptive approaches that FHH employ in reducing the impacts thereof. The approach informing the study combined two approaches; firstly, the `bottom-up' participatory research undertaken in three communities namely Inanda, Ntuzuma and Kwamashu; secondly, a rapid appraisal of policies, programs and institutions. The results were then triangulated using a micro-action planning workshop and a consultation process. A total of 84 small scale farmers who are actively involved in subsistence farming participated in the research study. From the empirical findings it is evident that climate change has manifested itself in floods and droughts and has been ranked extremely prevalent and frequent by 75% and 86% of the overall responses from the three study sites. The combination of these two extreme events has had negative impacts on food production and food accessibility. However, it has been found that FHH use asset based adaptation to modify and adjust their livelihoods as a way of coping with established threats. The eThekwini municipality has developed the Municipal Climate Change Protection Programme (eTMCCPP) with the purpose to mainstream climate change adaptation in the general city planning and development framework as well as to harmonize local urban responses to climate variability. However, only 48% of the participants have received any form of assistance and support from the Municipality. More needs to be done to help build capacity at household level and improve livelihoods of the local community particularly of Female headed households.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Geography. 24 March 2017
Keywords: Urban agriculture--South Africa--KwaZulu-Natal; Food security--South Africa--KwaZulu-Natal; Climate changes--South Africa--KwaZulu-Natal; Women and the environment--South Africa--KwaZulu-Natal; Women heads of households--South Africa--KwaZulu-Natal--Economic conditions